How can I become the best teacher? ELT instructors’ professional development preferences - YILMAZ VİRLAN, AYŞE (My University, 2023)
It is well acknowledged that one of the most significant things contributing to a successful career in language teaching is ongoing professional development. It is difficult to determine which tool is the most effective for the development of teachers because of the variety of current strategies that are still being debated in terms of their usefulness and practicability as professional development practices. Furthermore, the perspectives that teachers hold regarding professional development practices vary widely. In this work, various strategies for aiding the professional growth of ELT teachers at a foundation university in Istanbul are presented and discussed. Additionally, their preferences for varied practices that enhance teacher development were identified through a survey investigation. The data were collected through a survey questionnaire, and then they were analyzed to demonstrate both the similarities and differences in the approaches to teaching. The findings revealed that the degree to which teachers valued and made use of the activities differed significantly based on several factors, including their gender, age, years of teaching experience, the undergraduate field of study, and level of qualification. The findings could serve as the foundation for a proposal made to educators who are interested in developing their approach to teaching more professionally.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Eğitim Programları ve Öğretim; Social Sciences and Humanities; Education; Educational Sciences; Curriculum Development and Teaching Methods; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Professional Development; Teacher Training; Teacher Preferences